Facklamia ignava sp. nov., Isolated from Human Clinical Specimens - Collins, Matthew D. (American Society for Microbiology, 1998)
Two strains of a hitherto-undescribed gram-positive, catalase-negative coccus isolated from human sources were characterized by phenotypic and molecular taxonomic methods. Comparative 16S rRNA gene sequencing studies demonstrated that the unknown strains are genealogically identical and constitute a new line close to, but distinct from, Facklamia hominis. The unknown bacterium was readily distinguished from F. hominis by biochemical tests and electrophoretic analysis of whole-cell proteins. On the basis of phylogenetic and phenotypic evidence, it is proposed that the unknown bacterium be classified as Facklamia ignava sp. nov. The type strain of Facklamia ignava is CCUG 37419.